Preface - Imperatori, Andrea (Journal of Thoracic Disease, 2017)
EBUS-TBNA is recognized as the first step technique for mediastinal staging of non-small cell lung cancer (NSCLC). The reliability of mediastinal staging with EBUS-TBNA, as with other diagnostic techniques, largely depends on the accuracy of the procedure. The analysis of the data reported in the literature show a significant variation of EBUS-TBNA results in terms of diagnostic yield.